Corruption, rule of law, and environmental damage: Evidence from 177 countries, including Indonesia - Muhammad Abduh; Meita Istianda; Aos Kuswandi (Komisi Pemberantasan Korupsi, 2026)
This study examines whether corruption is associated with environmental damage and if the rule of law conditions this relationship, with particular attention to Indonesia’s relevance for anti-corruption policy in resource-linked sectors. Environmental damage is measured by reversing the Environmental Performance Index (EPI 2024) score (100 − EPI), so that higher values indicate worse conditions. Governance indicators come from the Worldwide Governance Indicators (WGI 2021–2023). We estimate an interaction model in which corruption (coded so higher values indicate higher corruption) and law enforcement strength (rule of law) jointly explain environmental damage, with income included as a control variable. Results show a positive corruption–damage association in baseline models and a statistically significant interaction term, indicating that the association varies across enforcement regimes. Indonesia is benchmarked within the sample and falls in the upper tail of environmental damage, with corruption above the median and rule-of-law strength around the middle of the distribution. The findings suggest that environmental policy in Indonesia should be integrated with anti-corruption controls through licensing, inspection, sanctioning, transparency, and extractive-sector governance.